Description of Knowledge of Pregnant Women About Anemia in Batu Malenggang Village, Hinai District, Langkat Regency - Tri Suci Dewi Wati; Adina Fistabilarawi (Science Midwifery, 2020)
According to the World Health Organization (2010), Indonesia ranks first with the highest maternal mortality rate (MMR) from maternal mortality (28%), anemia and chronic energy deficiency in pregnant women are the main causes of bleeding and infection which are the main factors of death in pregnant women. . Based on research data on the quality of the Indonesian population in 2011, the Maternal Mortality Rate (MMR) was still at 228/100.00 live births. Objective: To determine the level of knowledge of pregnant women about anemia in Batu Malenggang Village, Hinai District, Langkat Regency in 2014. This type of research is a descriptive survey. The research was conducted in June 2014, the research instrument was a questionnaire. The population of 35 pregnant women as well as the sample in this study (total sampling). The results showed that the level of knowledge of pregnant women about anemia in Batu Malenggang Village, Hinai District, in the good category was 7 people (20.0%), the sufficient category was 22 people (62.9%), and the less category was 6 people (17.1%). %). The highest level of knowledge of pregnant women about anemia in Batu Malenggang Village is the sufficient category as many as 22 people (62.9%). to prevent and reduce the risk of anemia in pregnancy.